2022
DOI: 10.1021/jacs.2c06827
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Photoaffinity Profiling of Omega-3 Signaling Lipid Probes Reveals Prostaglandin Reductase 1 as a Metabolic Hub in Human Macrophages

Abstract: The fish oil constituent docosahexaenoic acid (DHA, 22:6 n-3) is a signaling lipid with anti-inflammatory properties. The molecular mechanisms underlying the biological effect of DHA are poorly understood. Here, we report the design, synthesis, and application of a complementary pair of bio-orthogonal, photoreactive probes based on the polyunsaturated scaffold DHA and its oxidative metabolite 17-hydroxydocosahexaenoic acid (17-HDHA). In these probes, an alkyne serves as a handle to introduce a fluorescent repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The combined uses of these strategies has been addressed in numerous reports. [33][34][35][36] This alternative approach should significantly increase the yield for the semi-hydrogenation but at the same time introduce several new reactions and additional steps to the synthesis. The stereoselectivity of the Wittig reaction was also under question, but the stereoselectivity is usually very high or excellent, although there is no guarantee for that.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The combined uses of these strategies has been addressed in numerous reports. [33][34][35][36] This alternative approach should significantly increase the yield for the semi-hydrogenation but at the same time introduce several new reactions and additional steps to the synthesis. The stereoselectivity of the Wittig reaction was also under question, but the stereoselectivity is usually very high or excellent, although there is no guarantee for that.…”
Section: Chemistryselectmentioning
confidence: 99%
“…73 Most recent amongst this series of lipid probes are those described by van der Stelt and co-workers, who report pac probes for omega-3 fatty acids, docosahexaenoic acid (DHA) and its oxidative metabolite 17-hydroxy-DHA (17-HDHA) to profile their metabolic pathways in human macrophages. 74 Using the pac-DHA and pac-17-HDHA lipid probes (Fig. 3E), van der Stelt and co-workers showed for the first time that the enzyme prostaglandin reductase 1 (PTGR1), which is important in immune signaling cascades, binds to and uses 17-HDHA as a substrate.…”
Section: Papermentioning
confidence: 99%
“…This exciting work has expanded the repertoire of oxidative lipid substrates for this key lipid metabolic enzyme beyond the eicosanoids. 74…”
Section: Papermentioning
confidence: 99%
“…Further proteomic analysis revealed peroxiredoxin-1 as the most significant binding interactor of both DHEA and AEA probes. Recently, van der Stelt and colleagues designed bifunctional probes (pac-DHA and pac-17-HDHA) based on docosahexaenoic acid (DHA) and its oxidative metabolite 17-hydroxydocosahexaenoic acid (17-HDHA), respectively (Figure C) . These probes were used to map specific targets of the omega-3 signaling lipids in primary human macrophages, and it was found that 8 and 10 proteins were specifically labeled by pac-DHA and pac-17-HDHA, respectively.…”
Section: Photolabeling Group Located At the Lipid Hydrophobic Partmentioning
confidence: 99%
“…Recently, van der Stelt and colleagues designed bifunctional probes (pac-DHA and pac-17-HDHA) based on docosahexaenoic acid (DHA) and its oxidative metabolite 17- 4C). 33 These probes were used to map specific targets of the omega-3 signaling lipids in primary human macrophages, and it was found that 8 and 10 proteins were specifically labeled by pac-DHA and pac-17-HDHA, respectively. Further validations with the probe-enriched protein PTGR1 (prostaglandin reductase 1) revealed that the oxidative metabolite of 17-HDHA is a substrate of PTGR1, rather than 17-HDHA itself.…”
Section: Iiia Fatty Acidsmentioning
confidence: 99%